THE DEATH PENALTY IN THE PUNISHMENT SYSTEM OF TRADITIONAL KAZAKH LAW - G.R. Useinova; K.R. Useinova; A.T. Bazarbaeva; A.E. Zhainak (Хабаршы. Заң сериясы, 2019)
The article is devoted to the study and analysis of the institution of the death penalty in the traditional law of the Kazakhs. The traditional law of Kazakhs was formed under the influence of nomadic lifestyle and political and legal structure. The criminal law of the traditional nomadic society of Kazakhs is characterized by the presence of two basic principles. This is the principle of collective tribal responsibility and the principle of composition. By the period of the accession of Kazakhstan to Russia in the Kazakh customary law, there was the following system of punishments: death penalty, corporal punishment, shameful punishment, extradition of the guilty party of the victim, expulsion from the tribal community, Kun, Aip. Analysis of customary law shows that the death penalty under Kazakh customary law was applied very rarely and only with the consent of the Kurultai-people’s Assembly. This rule lasted until the 18th century. Starting from the second half of the 18th century, khans and sultans in Kazakh society began to use the death penalty more often, both against their political opponents and those who stubbornly disobey them. The analysis of historical and legal literature shows that in the traditional legal systems of Central Asia and Kazakhstan there were many types of capital punishment.